The anomalies of high-precision geochemical exploration in well AT2 area of Tahe Oil Field, Tarim Basin and its geological significance for production - Min YANG; Shuyang CHEN; Guojian WANG (Shiyou shiyan dizhi, 2021)
To evaluate the hydrocarbon potential of multiple traps in the middle and up oil groups of Triassic, an intensive oil and gas geochemical exploration has been carried out in the well AT2 area of the Tahe Oil Field of the Tarim Basin by the means of hydrocarbon microseepage-based high-precision geochemical exploration techniques.The geochemical indicators selected for this study were all active ones, including soil gas, physical adsorbed hydrocarbon gas and headspace gas.Near-surface soil samples were collected by means of a 0.25 km×0.25 km measuring grid, with a 0.1 km×0.1 km measuring grid over some key traps.Soil gas methane, physical adsorbed methane, and headspace methane were selected as the representative geochemical indicators, and their geochemical anomaly features over the well AT2 area were studied.Based on which, five integrated geochemical anomaly zones (consistent with five traps) were determined.The five integrated geochemical anomaly zones were ranked using a double-factor evaluation method combining geochemical and geological exploration evaluation parameters, and the hydrocarbon-bearing potential of these traps were evaluated, providing a geochemical basis for oil and gas rolling development of the well AT2 area.